Long-term energy transitions and international business: Concepts, theory, methods, and a research agenda - Doh, Jonathan; Budhwar, Pawan; Wood, Geoffrey (Journal of international business studies, 2021)
International business and management (IB/IM) scholars are increasingly calling for more research attention to subject matter that incorporates global-scale issues (Buckley, Doh, & Benischke, 2017). These calls have frequently focused on societal “grand challenges” that transcend discrete geographical locations and well-defined (typically short) time periods. The present long-term energy transition (LTE), characterized by a shift away from hydrocarbons and towards renewables, represents an important example of a multi-level, multi-actor global challenge that unfolds at the interface of business and society, and requires employing multiple conceptual lenses to process and understand. Researchers addressing such multi-faceted complex problems face a range of challenges related to theorizing, framing, modeling, and ultimately conducting empirical studies. Based on our collective work as IB scholars and journal editors, in this Perspective article we identify some of the challenges long-term energy transitions pose, reflect on how those challenges can be conceptualized, offer potential responses, and propose a future research agenda.